Research on the Creation of Cultural Ecology to Identity Brand Image in the Context of Recreation: Literature Review and Prospects - Ren, Meijiao; Roadkasemsri, Vuthipong (Journal of Ecohumanism, 2025)
In recent years,from cultural and ecological construction to urban identity and branding in the context of recreation industry has become an important research topic. The systematic literature review method is adopted to review 656 journal articles originated from China Knowledge Network (CNKI). The research review is conducted in terms of overall research characteristics, highly cited literature, theoretical foundations, existing problems, and research methods. The results of the literature analysis are systematically elaborated from the foundation of the recreation and culture tourism industry and related theories, domestic culture and ecology to the culture and ecology of Dongtang Town, historical and cultural analysis of the recreation and culture tourism brand, the current situation and problems of construction, and the analysis of the construction of hot springs recreation and culture industry. The study found that the development mode of "recreation" will continue to develop rapidly, and the development of recreation tourism will intensify. The development of Liaoning Dongtang Hot Spring Town needs to make full use of its original hot spring resources, perfectly integrate with the recreation industry, and shape a hot spring recreation brand with a sense of identity and belonging.